PENGEMBANGAN WISATA AGRO DI KOTO BARU KABUPATEN TANAH DATAR PROPINSI SUMATERA BARAT - Rais, Syafruddin (Universitas Pelita Harapan Medan, 2018)
This study aims to find components of agro tourism development in the district koto baru tanah datar west Sumatra province in of the plans that can for the development of tourism. This study uses qualitative descriptive research with reference to the concept of agro tourism. The population in this study is in the form of a social situation that koto baru tanah datar Â Â district with the participants there in, he Department of Tourism and Culture, as well as local travel industry, communities and institutions in the province of West Sumatra. Instruments in this study was the observation, and interviews with model coding, interpretation and congrulation.These results indicate that the development of agro-tourism that conserves natural resources, converting local technology, improve the economy and technology internshipKeywords:Tourism, agro tourism, stakeholder, Institutional